Innovative models of pension fund governance in the context of the global financial crisis. - Clark, G; Urwin, R (Palgrave Macmillan, 2010)
The global financial crisis has posed profound threats to pension welfare worldwide. This is particularly so in the United Kingdom with the closure of private defined benefit plans, and the heavy losses experienced by many defined contribution pension plan participants. Meeting these challenges has placed a premium on plan governance, given its link to fund performance. This paper begins by considering the academic literature on institutional change, including an analysis of the most common ways of responding to a changing environment. It is noted that the nature and scope of institutional response to a changing environment depends, in part, upon funds’ governance budgets, including time, expertise and common commitment. Our research on UK governance suggests that incremental adaptation has been the operative strategy augmented, in some cases, by the adoption of UK corporate governance practices. Three types of innovation in the governance of UK pension plans are identified: the transformation of decision-making, the pension buy-out and fiduciary management alongwith an emerging ‘new’ model of pension fund governance. In the penultimate section of this paper, lessons from UK best practice are drawn for institutions that face unprecedented challenges in realising the pension promise. Thereafter, we suggest a possible approach for regulators to strengthen the pension fund sector, based on improved disclosure, independent board chairs and the skills of board members.